ANALISIS STRATEGI PENGEMBANGAN EKOWISATA SERTA DAMPAKNYA TERHADAP MASYARAKAT SETEMPAT (STUDI KASUS: UMBUL BRONDONG, DESA NGRUNDUL, KECAMATAN KEBONARUM, KABUPATEN KLATEN) - Lia Kusumaningrum; Fayza Rachmalia; Muhammad Fadhil Ramadhan; Silvi Puspita Sari; Faradilah Farid Karim (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
Umbul Brondong as water-based ecotourism has high potential. Management of Umbul Brondong's tourism potential needs to be carried out so that ecotourism development can attract tourists to visit Umbul Brondong. This research aims to determine the potential of Umbul Brondong, evaluate the principles of ecotourism management, as well as ecotourism development strategies that need to be carried out by the Umbul Brondong management. This research uses a qualitative research method, namely research conducted to determine the perception and participation of local communities, visitor attraction and ecotourism development that has been carried out at the research location. In this research, a hypothesis is sought first to get a temporary answer. The results of the research show that ecotourism has 4A potential, namely amenities, attractions, accessibility, accessibility. Umbul Brondong has fulfilled the 5 principles of ecotourism, namely conservation, education, tourism, economy and community participation. Umbul Brondong development strategies include: improving roads to tourist attractions, increasing awareness and strengthening community institutions, increasing tourism promotion on a regional and national scale, as well as increasing conservation activities and improving the environment. Various strategies need to be implemented so that Umbul Brondong ecotourism continues to exist and becomes sustainable ecotourism.